2021
DOI: 10.1111/jpn.13652
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal effects of excessive dietary sulphur in feedlot cattle

Abstract: Sulphur (S) dietary excess can limit productive performance and increase polioencephalomalacia (PEM) incidence in feedlot cattle (FC). Sulphur excess ingested is transformed to hydrogen sulphide (H2S) by sulfo‐reducing ruminal bacteria (SRB), being high ruminal H2S concentration responsible for aforementioned damages. As the ruminal mechanisms involved in H2S concentrations increase have not been elucidated, this study aimed to evaluate the ruminal environment, and the association between ruminal H2S and dissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Feeding excessive levels of sulfur might result in undesirable consequences such as reduced feed consumption, diarrhea, and muscle spasms, lowering ruminant performance [15]. Furthermore, in ruminants, sulfite, a hazardous intermediate sulfur metabolite, may play a major role in the development of polioencephalomalacia (PEM) lesions [16]. The sulfite ion is a strong nucleophile that can destroy thiamine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding excessive levels of sulfur might result in undesirable consequences such as reduced feed consumption, diarrhea, and muscle spasms, lowering ruminant performance [15]. Furthermore, in ruminants, sulfite, a hazardous intermediate sulfur metabolite, may play a major role in the development of polioencephalomalacia (PEM) lesions [16]. The sulfite ion is a strong nucleophile that can destroy thiamine.…”
Section: Introductionmentioning
confidence: 99%
“…The sulfite ion is a strong nucleophile that can destroy thiamine. Thiamine deficiency appears to be a plausible risk factor in the etiology of PEM caused by excessive sulfur intake [16]. As a consequence, it is more attractive to feed the innovation of fresh cassava root using biological strategies to minimize HCN.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, rhodanese and mercaptopyruvate sulfurtransferase, two enzymes that promote HCN conversion, can be used to supply HCN as a nitrogen source for microbial production 14 . The rumen environment would benefit from the addition of nitrogen supply with fermentable starch from cassava, which would also improve microbial growth on digestibility 34 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that during the degradation process, amino acids containing sulfur (S) groups, including methionine and cysteine, are catabolized by rumen microbes to produce H 2 S [76]. Under this assumption, the high production of H 2 S with the ensiled forage of the Amarillo genotype may be associated with the concentration and degradation of the amino acids that comprise it, especially those amino acids that contain sulfur [77]. Meanwhile, the low H 2 S production with the Montesa silage may be attributable to the addition of GAA, since there was an interaction between the genotype and the addition of GAA, and it has been reported that the use of additives may influence the reduction in H 2 S production in the rumen [78].…”
Section: Ruminal Hydrogen Sulfide (H 2 S) Productionmentioning
confidence: 99%